2015
DOI: 10.1016/j.conengprac.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Robust FDI for fault-tolerant thrust allocation with application to spacecraft rendezvous

Abstract: a b s t r a c tThis paper deals with the design and validation of an active fault-tolerant control system to detect, isolate and accommodate a single thruster fault affecting the thruster-based propulsion system of an autonomous spacecraft. The proposed method consists of a fault detector for robust and quick fault detection, a two-stage hierarchical isolation strategy for fault isolation, and an online control allocation unit scheduled by the isolation scheme for fault tolerance. A new factorization approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Recent studies [4], [8] demonstrated that thrusters faults can be successfully diagnosed using the model that links the actuator (thruster) commands with the IMU measurement. This approach is retained in this work.…”
Section: The Fdi Unit a Modelling Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies [4], [8] demonstrated that thrusters faults can be successfully diagnosed using the model that links the actuator (thruster) commands with the IMU measurement. This approach is retained in this work.…”
Section: The Fdi Unit a Modelling Issuesmentioning
confidence: 99%
“…This paper overcomes this problem. The proposed strategy follows the study presented in [4], i.e. NL-UIO and control allocation techniques are used to diagnose and accommodate thruster faults.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the work in [9] addresses the development of a CA-based FTC solution for flexible satellites. In [10,11], the classical SIMPLEX-based CA algorithm is changed by the Nonlinear Inverse Pseudo Control (NIPC) solution to improve the FTC performances of the terminal rendezvous phase of the Mars Sample Return mission. An alternative solution can also be found in [12,13] by acting at the guidance level.…”
Section: B Antecedents and Paper Contributionmentioning
confidence: 99%
“…In general, FTC methods are classified into two types: passive fault tolerant control (PFTC) and active fault tolerant control (AFTC) schemes (Allerhand & Shaked, 2015;Cao, Chen, & Misra, 2014;Castaldi, Mimmo, & Simani, 2014;Fonod et al, 2015;Hu, Xiao, & Friswell, 2011;Jia, Chen, Zhang, & Li, 2015;Li & Yang, 2012;Liu, Qiu, Cui, & Sun, 2016;Marino, Scalzi, Tomei, & Verrelli, 2013;Mekki, Benzineb, Boukhetala, Tadjine & Benbouzid, 2015;Wang, Jing, Karimi, & Chen, 2015;Xiao, Hu, & Zhang, 2012). The similarities and differences between these two FTC design methodologies can be found in Jiang and Yu (2012).…”
Section: Introductionmentioning
confidence: 98%